2012
DOI: 10.1109/t-affc.2011.25
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Database for Affect Recognition and Implicit Tagging

Abstract: Abstract-MAHNOB-HCI is a multimodal database recorded in response to affective stimuli with the goal of emotion recognition and implicit tagging research. A multimodal setup was arranged for synchronized recording of face videos, audio signals, eye gaze data, and peripheral/central nervous system physiological signals. Twenty-seven participants from both genders and different cultural backgrounds participated in two experiments. In the first experiment, they watched 20 emotional videos and self-reported their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
849
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,240 publications
(946 citation statements)
references
References 40 publications
10
849
1
2
Order By: Relevance
“…Research toward such neurophysiologybased implicit tagging approaches of multimedia content has suggested its feasibility. [21,22] Liberati et al [23] showed that aBCI can be used for the communication of emotional responses toward a certain object. They 27] However, such stimulus-independent passive approaches (see below) might turn into active approaches, for example when players realize that their affective state has an influence on game parameters, and therefore begin to self-induce states to manipulate the gaming environment according to their preferences.…”
Section: Brain-computer Interfaces 67mentioning
confidence: 99%
“…Research toward such neurophysiologybased implicit tagging approaches of multimedia content has suggested its feasibility. [21,22] Liberati et al [23] showed that aBCI can be used for the communication of emotional responses toward a certain object. They 27] However, such stimulus-independent passive approaches (see below) might turn into active approaches, for example when players realize that their affective state has an influence on game parameters, and therefore begin to self-induce states to manipulate the gaming environment according to their preferences.…”
Section: Brain-computer Interfaces 67mentioning
confidence: 99%
“…Therefore, the results are not reliable on naturalistic conditions regarding illumination, headpose variations and nature of expressions. Nevertheless, there are non-posed datasets to test naturalistic expressions such as SEMAINE [23], MAHNOB-HCI [21] or DECAF [52]. In these cases the illumination and head-pose variation problems are taken into account depending on the aim of the study.…”
Section: Facial Emotion Recognition Approachesmentioning
confidence: 99%
“…The work in [20] considers both types of data using the MAHNOB-HCI database [21]. The EEG signal was captured using 32 sensors and the power spectral density was extracted from overlapping one second windows.…”
Section: Facial and Eeg Emotion Recognition Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The users' behavior and spontaneous reactions to multimedia data can provide useful information for multimedia indexing with the following scenarios: (i) direct assessment of tags: users spontaneous reactions will be translated into emotional keywords, e.g., funny, disgusting, scary [3], [4], [5], [6]; (ii) assessing the correctness of explicit tags or topic relevance, e.g., agreement or disagreement over a displayed tag or the relevance of the retrieved result [7], [8], [9], [10]; (iii) user profiling: a user's personal preferences can be detected based on her reactions to retrieved data and be used for re-ranking the results; (iv) content summarization: highlight detection is also possible using implicit feedbacks from the users [11], [12].…”
Section: Introductionmentioning
confidence: 99%